2014
DOI: 10.1101/006312
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Establishment of regions of genomic activity during theDrosophilamaternal to zygotic transition

Abstract: We describe the genome-wide distributions and temporal dynamics of nucleosomes and post-translational histone modifications throughout the maternal-to-zygotic transition in embryos of Drosophila melanogaster. At mitotic cycle 8, when few zygotic genes are being transcribed, embryonic chromatin is in a relatively simple state: there are few nucleosome free regions, undetectable levels of the histone methylation marks characteristic of mature chromatin, and low levels of histone acetylation at a relatively small… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
61
1
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(68 citation statements)
references
References 53 publications
5
61
1
1
Order By: Relevance
“…Whether it is the process of enhancer transcription that is important (Wilson et al 1996;Cho et al 1998;Kaikkonen et al 2013) or the eRNA itself (Lam et al 2013;Melo et al 2013;Li et al 2014) may vary from one locus or context to another. Alternatively, it may be a nonfunctional consequence of the random engagement of Pol II to open chromatin (Struhl 2007).…”
mentioning
confidence: 99%
“…Whether it is the process of enhancer transcription that is important (Wilson et al 1996;Cho et al 1998;Kaikkonen et al 2013) or the eRNA itself (Lam et al 2013;Melo et al 2013;Li et al 2014) may vary from one locus or context to another. Alternatively, it may be a nonfunctional consequence of the random engagement of Pol II to open chromatin (Struhl 2007).…”
mentioning
confidence: 99%
“…Many transcription factors have strong activation domains, putting accessible enhancer regions at risk for unwarranted activation. For example, Zld has high transactivation potential and likely recruits the histone acetyl transferase CBP that mediates H3K27ac (Hamm et al 2015;Stampfel et al 2015), consistent with H3K27ac being present during enhancer priming by Zld (Li et al 2014). Strikingly, we showed that Zld is still bound to DV enhancers during DV patterning, yet these enhancers have no or low H3K27ac and remain uninduced in parts of the embryo.…”
Section: A Role For Repressors In Keeping Poised Enhancers Inactivementioning
confidence: 55%
“…Thus, the low levels of H3K27ac and the reduced access to transcription factors that we observe for zen, dpp, and tld must be to some extent the result of Dl-mediated repression. (Li et al 2014) show that H3K27ac levels are accumulating early and gradually during development, and thus, some H3K27ac is present during enhancer priming by Zld at cell cycles 8 and 12. In contrast, H3K4me1 and H3K27me3, which mark poised enhancers, are only detectable after Dl-dependent transcription begins at stage 5 or cell cycle 14 (shaded in gray).…”
Section: A Role For Repressors In Keeping Poised Enhancers Inactivementioning
confidence: 99%
See 2 more Smart Citations